Comprehensive investigations of cerebral hemodynamic responses in CSVD patients with mental disorders: a pilot study - Wen, Dan; Xu, Yong (Frontiers in Psychiatry, 2023)
Although a portion of CSVD patients present mental disorders, there is currently a lack of appropriate technologies to evaluate the brain functions that are relevant to neuro-vascular coupling. Furthermore, the objective criteria diagnosis to distinguish the CSVD induced-mental disorders and psychiatric diseases have not been established thus far.In this study, we report the first comprehensive investigations on the cerebral hemodynamics of the CSVD patients who also presented mental disorder. Two CSVD patients with similar magnetic resonance imaging(MRI) outcomes, but with not identical mental symptoms, participated in this study. The patients were instructed to perform the verbal fluency task (VFT), high-level cognition task (HCT), as well as voluntary breath holding (VBH). fNIRS instrument was used to measure the cerebral oxygenation responses. Additionally, diffuse correlation spectroscopy (DCS) was used to measure the cerebral blood flow (CBF) responses. As the comparison, both technologies were applied to a healthy subject.With the fNIRS measurement, both CSVD patients presented abnormal cerebral oxygenation responses during the VFT, HCT and VBH tasks. Moreover, the patient with cognition impairment shows fluctuations in CBF during these tasks. By contrast, the patient without cognition impairment mostly present typical CBF responses during the tasks,which is consistent with the healthy subject.The cognitive impairment in CSVD patients may due to the decoupling between the neurons and cerebrovascular, subsequently affecting the autoregulation capacity. The combination of the fNIRS and DCS provides a comprehensive evaluation of the neuro-vascular coupling, hence has great potential in diagnose of cerebrovascular or psychiatric diseases.